Women-led firms and the gender gap in top executive jobs - Linda A. Bell (Institute for the Study of Labor (IZA), 2005)
Using data on Executive Compensation from Standard and Poor's ExecuComp, this paper explores the gender gap in top executive jobs and the effect of women CEOs, Chairs, and Directors on the pay of other women executives. The results show a narrowing of the uncorrected gender pay gap from the mid-1990s. Women top executives earn between 8% to 25% less than male executives after controlling for differences in company size, occupational title, and industry. The magnitude of the gender pay gap is statistically related to the gender of the Chief Executive and Corporate Board Chair. Women CEO and Board Chairs bring more top women and at higher pay than is found in non-women-led firms. Specifically, female executives in women-led firms earn between 10-20% more than comparable executive women in male-led firms and are between 3-18% more likely to be among the highest five paid executives in these firms as well. The paper thereby provides strong empirical evidence that women leaders are associated with positive outcomes for women executives in substantive and important ways.
Keywords: J11; J16; J33; J70; J71; J78; 330; executive compensation; gender discrimination; labor market institutions